2006
DOI: 10.1182/blood-2006-03-012013
|View full text |Cite
|
Sign up to set email alerts
|

The THAP–zinc finger protein THAP1 regulates endothelial cell proliferation through modulation of pRB/E2F cell-cycle target genes

Abstract: We recently cloned a novel human nuclear factor (designated THAP1) from postcapillary venule endothelial cells (ECs) that contains a DNA-binding THAP domain, shared with zebrafish E2F6 and several Caenorhabditis elegans proteins interacting genetically with retinoblastoma gene product (pRB). Here, we show that THAP1 is a physiologic regulator of EC proliferation and cell-cycle progression, 2 essential processes for angiogenesis. Retroviral-mediated gene transfer of THAP1 into primary human ECs inhibited prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
163
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(173 citation statements)
references
References 42 publications
8
163
1
1
Order By: Relevance
“…We found that human THAP1 is an endogenous physiological regulator of endothelial cell proliferation and G 1 /S cell cycle progression, which modulates expression of sev-eral pRb 4 /E2F cell cycle target genes. In addition, we identified RRM1, a G 1 /S-regulated gene required for S-phase DNA synthesis, as a direct transcriptional target of endogenous THAP1 (10). These data provided the first links in mammals between THAP proteins, cell proliferation, and pRB/E2F cell cycle pathways and complemented genetic data previously obtained in model animal organisms.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…We found that human THAP1 is an endogenous physiological regulator of endothelial cell proliferation and G 1 /S cell cycle progression, which modulates expression of sev-eral pRb 4 /E2F cell cycle target genes. In addition, we identified RRM1, a G 1 /S-regulated gene required for S-phase DNA synthesis, as a direct transcriptional target of endogenous THAP1 (10). These data provided the first links in mammals between THAP proteins, cell proliferation, and pRB/E2F cell cycle pathways and complemented genetic data previously obtained in model animal organisms.…”
supporting
confidence: 70%
“…We recently demonstrated that THAP1 is a physiological regulator of cell proliferation. Silencing of THAP1 by RNA interference in human primary endothelial cells resulted in inhibition of G 1 /S cell cycle progression and down-modulation of several pRb/E2F cell cycle target genes, including RRM1, a gene activated at the G 1 /S transition and essential for S-phase DNA synthesis (10). We showed that the THAP zinc finger of THAP1 recognizes a consensus THAP1-binding site in the RRM1 promoter and that endogenous THAP1 associates in vivo with this site, indicating that RRM1 is a direct target gene of THAP1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations